Modul Fisika Berbasis SETS (Science, Environment, Techology, and Society) dan Pengaruhnya Terhadap Literasi Sains Peserta Didik - Fiskia Ruzaina; Helmi; Muhammad Arsyad (Postgraduate, University of Mataram, 2025)
This research is a type of Research and Development (R&D) employing the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The aim of this research is to develop a SETS-based physics module and to examine its validity, practicality, and effectiveness in improving students’ scientific literacy skills. Validation was conducted by three experts who assessed both the module and the scientific literacy test. The practicality of the module was evaluated by eight physics teachers. To determine the effectiveness of the module, a true experimental design was used, specifically the posttest-only control group design, involving two groups: an experimental class (28 students) and a control class (27 students), both from Grade 10 at SMA Muhammadiyah Kalosi. The research findings revealed that: the module was valid and appropriate for use; teacher responses indicated the module was highly practical; and the results of an independent samples t-test showed a t-value of 5.448, which exceeded the t-table value of 2.006 at a 5% significance level. Based on these results, the SETS-based physics module is considered valid, highly practical, and effective in enhancing students’ scientific literacy skills.